Effect of alloying on transformation temperatures and magnetoplasticity in Ni-Mn-Ga alloys - Glavatska, N.; Dobrinskiy, A.; Glavatskiy, I.; Urubkov, I.; Ge, Y.; Soderberg, O.; Hannula, S.-P. (Functional Materials, 2006)
In this work, the alloying effect ternary Ni-Mn-Ga alloys on the phase transformation temperatures and magnetoplasticity potential has been investigated. Several ternary and quaternary off-stoichiometric compositions of Ni-Mn-Ga alloys and Ni-Mn-Ga-X ones (where X = Si, in, Co, Fe) have been studied. The phase transformation temperatures were